Epidemiology of Selected Childhood Cancers in the Context of Air Pollution in Gdańsk - Góra, Dariusz Jerzy; Ziernicka-Wojtaszek, Agnieszka; Kupiec, Jerzy Mirosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The long-term effects of ambient air pollution are of concern, as many pollutants are carcinogenic, potentially causing various types of cancer, including childhood cancers. The aim of this article is to discuss the incidence of selected cancers in children and adolescents in Gdańsk in the context of air pollution. The research material consists of data on the incidence of selected cancers in children and adolescents aged 0-18 years and data on average annual air pollution concentrations in Gdańsk. Spearma`s rank correlation coefficient was used.
Keywords: childhood cancers; air pollution; particulate matter; bone cancer; leukemia